Theoretical Approaches on Religion, Ideology, and Governance in Israel's Political Landscape - Katz, Yaron (Randwick International of Social Science Journal, 2025)
This paper explores the conflict between conservatism and modern society in Israel, focusing on the ideological divide between secular and ultra-Orthodox (Haredi) communities. Drawing on conservatism theory, modernization theory, and conflict theory, the study analyzes how these forces shape political, social, and cultural landscapes. The persistence of Haredi conservatism, rooted in traditional values and religious autonomy, contrasts with the progressive demands of a modernizing Israeli society, creating tensions that manifest in governance challenges, military service exemptions, and debates over public policy. The analysis highlights how conservatism provides stability and identity while resisting transformative pressures, while modernization drives gradual integration through workforce participation, education, and economic shifts. Conflict theory underscores the societal polarization and competition for power between ideological groups, complicating efforts to foster inclusivity and unity. By examining the Israeli context, the paper offers broader insights into the global dynamics of conservatism and modernity, emphasizing the importance of adaptive governance, equitable representation, and inclusive dialogue to address these tensions and promote societal cohesion. By examining the interactions between tradition and progress, these frameworks underscore the necessity of finding a balance between preserving cultural identity and embracing the demands of modernity to achieve long-term stability and inclusivity.